Displacement, Identity and Belonging: An Arts-Based, Auto/Biographical Portrayal of Ethnicity and Experience - Cutcher, Alexandra J (Springer, 2016)
Displacement, Identity and Belonging is a book about difference. It deals with ethnicity, migration, place, marginalisation, memory and constructions of the self. The arts-based and auto/biographical performance of the many voices in the text compliment and interrupt each other to create a polyvocal rendition of experience. The text unfolds through fiction, memoir, legend, artworks, photographs, poetry and theory, historical, cultural and political perspectives. As such, it is a book that confronts what an academic text can be. Written in the present tense, it weaves its narrative around one small Hungarian migrant family in Australia, who are not particularly special or extraordinary. Their experience may appear, at least on first blush, to be paralleled by the post-war diasporic experience for a range of nations and peoples. However in many ways, this is not necessarily so. It is this crucial aspect, of the idiosyncrasies of difference that is at the core of this work. The layering of stories and artworks build upon each other in an engaging and accessible reading that appeals to a multitude of audiences and purposes. The book makes significant contributions to the literature on qualitative research, and in particular to arts-based research, auto/biographical research and autoethnographic research. Displacement, Identity and Belonging is in itself an experience of journey in the reading, powerfully demonstrating a life forever in transit. This work can be used as a core reading in a range of courses in education, teacher education, ethnicity studies, cultural studies, sociology, psychology, history and communication or simply for pleasure.